Quarantinescapes - Eftimov, Yordan (Sledva : NBU Journal of Humanities and Arts, 2020)
A triptych comprised of micro-essays from the first days of the quarantine announced in Bulgaria on March 13, 2020, due to the COVID-19 pandemic. The focus is on the acute experience, that is, on the imagery of the world in our mind, on the perception of reality shaped by memory.